IDENTIFICATION OF ACCESSIBILITY INDEX CHANGES IN LEBAK BULUS AREA AND THEIR IMPACTS ON LAND USE - Yubi Nabiilah, Bunga
Along with the operation of MRT transportation from the city center to the outskirts of the city, making it easier to travel to the outskirts of the city so that the suburban area has considerable appeal as a center of activity. The purpose of this research is to analyze the accessibility of the Lebak Bulus area due to changes in public transportation infrastructure with the operation of the MRT (Mass Rapid Transit). Identification is also carried out to determine the impact of changes in Land Use that occur due to changes in accessibility to the Lebak Bulus area within a radius of 1 km from the MRT station, analysis of land use changes is carried out based on aspects of land function, Building Area Coefficient, and asset value. The implementation of this study was carried out using a quantitative descriptive approach. The model used is Hansen Gravity Model, while the variables used are activity measures and travel time Calculations of accessibility and land use are carried out for two timeframes, namely before the operation of the MRT in 2014 and after the operation of the MRT in 2021. The results of the analysis of accessibility changes based on the Hansen Gravity Model show that the accessibility of car users decreased by 66%, motorcycle users decreased by 26%, and public transportation users increased by 69%. The most significant changes occurred in Commercial Activities where the land area increased by 52% and the building area increased by 62%. Correlation test shows that changes in accessibility that occur have a significant effect on building area and land area in the Lebak Bulus area. This proves that the Accessibility change supports the activity change in that area. With changes in activities in the existing land use, the composition of the land in the area changes to a more profitable direction, both in terms of usability and commercial terms.